Analysis of Zakat Community Development (ZCD) Management in Empowering Poor Communities: Case Study at Badan Amil Zakat Nasional (BAZNAS) West Nusa Tenggara Province - Riyan Azis Firmansyah; Busaini Busaini; Adhitya Bagus Singandaru (Experimental Student Experiences, 2023)
This research aims to determine the empowerment of poor communities through the Zakat Community Development (ZCD) program in West Nusa Tenggara Province, which is a program from the National Zakat Amil Agency (BAZNAS). The method used in this research is a qualitative research method with a type of field research. The data collection techniques used were in-depth interviews, documentation and observation. The results of this research show that community empowerment through the Zakat Community Development (ZCD) program initiated by the Central BAZNAS is already running in West Nusa Tenggara Province, this is proven by the development of businesses and assistance from the distribution of zakat funds through this program, such as in the economic sector,  education, health, religious or da'wah and humanitarian or social. This research also shows that the management of the Zakat Community Development (ZCD) program carried out by BAZNAS is running in accordance with the operational standards that have been created. The factors that hinder the success or failure of the ZCD program include the absence or lack of willingness to progress from the community, the village or region not accepting the program, lack of adequate facilities and lack of support from stakeholders.